Differential Responses of Embryonic and Postnatal Tendon Cells to IL-1beta Treatment: Implications for Scarless Healing. - Graybeal, Kaori. (2017)
Abstract: Adult and postnatal tendons heal poorly, forming scar tissue with aberrant properties. In contrast, embryonic tendons heal in a scarless manner, with restoration of native tissue properties. Investigation of scarless embryonic tendon healing may lead to strategies for improving adult tendon healing. We probed differences in embryonic and postnatal tendon cell responses to wound-related environmental factors, as well as potential mechanisms that may regulate their respective responses. Factors we tested included IL-1beta treatment, substrate elastic modulus, and extracellular matrix composition. We found that postnatal tendon cells have higher expression of inflammatory mediators and matrix metalloproteinases than embryonic tendon cells, both at baseline and in response to IL-1beta treatment, and that this disparity may be due to differences in IL-1 receptor profiles. The long-term goal of this project is to develop strategies to redirect adult scarred tendon healing outcomes toward more embryonic-like scarless tissue regeneration.; Thesis (M.S.)--Tufts University, 2015.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Catherine Kuo.; Committee: David Kaplan, and Li Zeng.; Keyword: Biomedical engineering.